Age and growth of oriental sole, Brachirus orientalis (Bloch & Schneider, 1801), in the Persian Gulf (Soleidae) (Ocean and Coastal Research, 2021)
The age and growth parameters are important biological indices in fish biology, fishery management, and aquaculture (Ghanbarzadeh et al., 2013, 2014, 2017). In practice, the age and growth parameters of fish are typically studied by examining catches at monthly intervals (Keivany et al., 2012; Keivany and Daneshvar, 2016).